Effective finite-difference modelling methods with 2-D acoustic wave equation using a combination of cross and rhombus stencils. Issue 3 (4th July 2016) - Wang, Enjiang; Liu, Yang; Sen, Mrinal K.
Abstract: The 2-D acoustic wave equation is commonly solved numerically by finite-difference (FD) methods in which the accuracy of solution is significantly affected by the FD stencils. The commonly used cross stencil can reach either only second-order accuracy for space domain dispersion-relation-based FD method or (2 M )th-order accuracy along eight specific propagation directions for time–space domain dispersion-relation-based FD method, if the conventional (2 M )th-order spatial FD and second-order temporal FD are used to discretize the equation. One other newly developed rhombus stencil can reach arbitrary even-order accuracy. However, this stencil adds significantly to computational cost when the operator length is large. To achieve a balance between the solution accuracy and efficiency, we develop a new FD stencil to solve the 2-D acoustic wave equation. This stencil is a combination of the cross stencil and rhombus stencil. A cross stencil with an operator length parameter M is used to approximate the spatial partial derivatives while a rhombus stencil with an operator length parameter N together with the conventional second-order temporal FD is employed in approximating the temporal partial derivatives. Using this stencil, a new FD scheme is developed; we demonstrate that this scheme can reach (2 M )th-order accuracy in space and (2 N )th-order accuracy in time when spatial FD coefficients and temporal FD coefficients are derived from respective dispersion relation using Taylor-series expansion (TE) method. To further increase the accuracy, we derive the FD coefficients by employing the time–space domain dispersion relation of this FD scheme using TE. We also use least-squares (LS) optimization method to reduce dispersion at high wavenumbers. Dispersion analysis, stability analysis and modelling examples demonstrate that our new scheme has greater accuracy and better stability than conventional FD schemes, and thus can adopt large time steps. To reduce the extra computational cost resulting from adopting the new stencil, we apply the variable spatial operator length schemes. Adopting our new FD scheme, characterized by new stencil, LS-based optimization, variable operator lengths and larger time step, modelling efficiency is significantly improved.